Ho'i Hou Ka Mauli Ola : Pathways to Native Hawaiian Health - Look, Mele A.; Lee, Winona K. Mesiona (Hawaiʻinuiākea monograph ;, 2017)
This pioneering collection highlights the historic, groundbreaking, and fascinating work done by doctors, researchers, and healthcare providers to improve the life of Native Hawaiians and Pacific Islanders. The relevance of their work impacts all of us regardless of ethnicity because the discoveries made in the search for solutions to health problems, cures to diseases, and improvements to healthcare benefit all who call Hawaiʻi, as well as the broader Pacific, home. The majority of the thirty-three contributors are affiliated with the Department of Native Hawaiian Health of the John A. Burns School of Medicine at the University of Hawaiʻi at Mānoa and represent many disciplines, strategies, and programs whose research, findings, and projects are built on the contributions of pioneers in medicine and healthcare in Hawaiʻi. As such, this book is dedicated to the late Richard Kekuni Blaisdell and includes an interview with him, bringing to the fore his essential voice on Native Hawaiian health. Mauli means life, heart, spirit, our essential nature. Ola means well-being, healthy. "Hoʻi hou ka mauli ola," or, bringing back the state of vibrant health, is the chief objective and the passion of the contributors. In addition to interviews, the volume includes historical information, personal narratives, mele oli, research findings, and descriptions of community programs.